Profiling of Religious Personality through Character Management Representations - Muhammad Sahlan (Journal of Research in Educational Management, 2023)
This study aims to find out how the profiling religious personality through managing character representations, considering the current condition of character problems in Indonesia is very deplorable. Therefore, there needs to be a new breakthrough in fixing this problem. This research uses a qualitative case study type approach carried out through observation, interviews and documentation. The data analysis technique starts from presenting the data, reducing the data and drawing conclusions. The results of the study show that; 1) Planning for character education for students at SMP Bhakti Pertiwi, is carried out by establishing the school's vision and mission, organizational structure, planning the system, preparing teachers and staff and their skills, then forming systems and strategies character education; 2) The implementation of character education with the McKinsey framework in forming the religious character and discipline of students at SMP Bhakti Pertiwi is by internalizing and integrating all character values ​​in all intra-curricular and extra-curricular activities of the school.